A prospective analysis of post mastoidectomy cavity complications - Rajan, Dhanya; James, Susan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2019)
Background: The main aims of surgical treatment of chronic middle ear suppuration are elimination of disease process, reconstruction of hearing mechanism and prevention of complications. The objective of this study is to find out the incidence of cavity problems after open cavity mastoidectomy. To evaluate perioperative factors involved in the causation of cavity problems. Methods: A prospective analytical study was conducted among 78 patients came for open mastoidectomy admitted in department of ENT. Each patient had a follow up upto three months at twice weekly intervals. In this study a borderline healing period of three months (12 weeks) was given for the complete epithelialisation of an open mastoid cavity. SPSS was used for analysis. Results: The incidence of postoperative cavity problems in our set up is 26.92%. Youngest patient to undergo mastoidectomy was a 4-year-old boy. The youngest patient who presented with cavity problem was of 7years. 59 (75.64%) had sclerotic mastoid and 10 (12.82%) had cellular mastoid and 9 (11.53%) had diploeic mastoid. Hence out of the 21 postoperative mastoid cavity problems, 5 cases had large postoperative cavity, 18 cases had high facial ridge, 1 case had stenosis of meatoplasty, 17 cases had exposed middle ear and eustachian tube and 17 had postoperative granulations. Conclusions: There should be complete exenteration of disease from the middle ear and mastoid. An adequately lowered facial ridge is an essential step to attain a dry cavity.